A Highly Sensitive Green Analytical UHPLC-MS/MS Method for the Quantification of Trace Level of N-Nitroso Meglumine Impurity in Tafamidis Meglumine Applying the Quality by Design - Raghuvaran, G.; Satla, Shobha Rani (Asian Journal of Chemistry, 2025)
Tafamidis meglumine is utilized for managing transthyretin amyloidosis (ATTR amyloidosis), a condition arising from improperly folded transthyretin proteins that impact the cardiac and neurological systems. A byproduct identified as N-nitroso megulamine (NNM), classified as a nitroso amine, may exist throughout the manufacturing procedure. To meet the requirements of green analytical principles, NNM quantification was achieved via UHPLC utilizing an Luna column (4.6 mm × 150 mm ID, 3.0 µm particle size) at a flow rate of 0.8 mL/min in isocratic mode. The central composite design experimental paradigm was adopted to improve the analytical parameters using design expert statistical software, with statistical significance quantified at p-values < 0.05%. The elution methodology included the ionization process utilizing heated ESI in positive ion mode, with identification and quantification executed in MRM mode, transitioning at m/z 223.20 to 59.10. A high degree of linearity, indicated by r2 > 0.990, was established from the quantification limit (0.25 µg/mL) to 150% (1.893 µg/mL) of NNM. The validation procedure was carried out in accordance with ICH Q2 guidelines and addressed the parameters of system suitability, accuracy, linearity, detection limit, quantitation limit, specificity and precision. Recovery rates are varied between 99% and 128%. Green assessment tools such as Analytical Eco-Scale, GAPI and AGREE endorse the sustainability of the proposed method.